The effect of in vivo growth on the cellular and extracellular components of the marine bacterial pathogen Photobacterium damsela subsp. piscicida - Bakopoulos, V (Journal of fish diseases, 2004)
Photobacterium damsela subsp. piscicida, the causative agent of fish pasteurellosis, was grown in vivo. Bacterial cells and extracellular products (ECPs) were analysed via electrophoresis and immunoblot analysis, using specific sea bass antisera. Growth in vivo induced the synthesis of unique bacterial cell proteins at > 206, 206, 21.3, 18, 7.6 and < 7.6 kDa. Sea bass serum raised against live bacterial cells of the pathogen and especially a sea bass serum raised against formalin-inactivated bacterial cells grown in a specific novel medium recognized the novel antigens at > 206 (associated with iron sequestration), 21.3, 7.6 and < 7.6 kDa, suggesting that the latter medium conserves the synthesis of natural bacterial cell proteins in vitro. In vivo growth of the pathogen induced the synthesis of more toxic ECPs in comparison with in vitro growth and an inverse correlation between total protein concentration in the ECPs and toxicity per unit of protein was observed. Substrate-polyacrylamide electrophoresis revealed the presence of in vivo synthesized ECPs of the pathogen (proteases) at 175, 132, < 79 and 48.3 kDa. Histological examination of tissues isolated from fish injected with these ECPs revealed inflammatory and necrotic lesions in the spleen, liver, head kidney, intestine and heart as soon as 48 h post-introduction of the ECPs